2007
DOI: 10.1016/j.radphyschem.2006.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Cryoradiolytic reduction of heme proteins: Maximizing dose-dependent yield

Abstract: Radiolytic reduction in frozen solutions and crystals is a useful method for generation of trapped intermediates in protein based radical reactions. In this communication we define the conditions which provide the maximum yield of one electron reduced myoglobin at 77 K using 60 Co γ-irradiation in aqueous glycerol glass. The yield reached 50% after 20 kGy, was almost complete at ∼160 kGy total dose, and does not depend on the protein concentration in the range 0.01 -5 mM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
(61 reference statements)
1
16
0
Order By: Relevance
“…Recent studies with other heme proteins (see (27-29) and references therein) have provided evidence for spectral and/or structural changes induced by intense X-ray radiation. The chemical, spectral and structural results described here for Thermus cytochrome ba 3 can be understood in terms of the following: First , crystalline, oxidized cytochrome ba 3 can be fully reduced by a short incubation in buffered cryo-solution containing ∼10 mM Na 2 S 2 O 4 , or alternatively, crystals can be formed from reduced protein in dithionite-containing mother liquor and maintained O 2 -free.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies with other heme proteins (see (27-29) and references therein) have provided evidence for spectral and/or structural changes induced by intense X-ray radiation. The chemical, spectral and structural results described here for Thermus cytochrome ba 3 can be understood in terms of the following: First , crystalline, oxidized cytochrome ba 3 can be fully reduced by a short incubation in buffered cryo-solution containing ∼10 mM Na 2 S 2 O 4 , or alternatively, crystals can be formed from reduced protein in dithionite-containing mother liquor and maintained O 2 -free.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of published works utilized γ-irradiation from 60 Co source for cryoradiolytic reduction of cytochromes P450 and other heme proteins (59,62,63). Photons from this source, with energies 1.13 and 1.3 MeV, interact with atoms with low Z (atomic mass) mostly through inelastic Compton scattering with emission of lower energy photon, and generation of free electron and cation radical as primary products of this scattering (60).…”
Section: Introductionmentioning
confidence: 99%
“…The actual concentration of generated electrons in ice at 77 K may be several times lower because of recombination of electrons with parent radicals, and the typical doses used in cryoradiolytic reduction range from 2 to 10 Mrad. Recombination of electrons with radicals also results in a saturation behavior of cryoradiolytic reduction with increasing dose, and the yield for metalloproteins usually is not improved by prolonged irradiation with the doses higher than 4 – 6 Mrad dose (63,64). …”
Section: Introductionmentioning
confidence: 99%
“…This undesired radiation-induced change is observed for the ferric metMb state during crystallographic data collection [8] [12] [62]. Already in the 1970s Gasyna showed that ferric Mb can be one-electron-reduced by 60 Co g-irradiation in frozen solution at 77 K [63], and a more detailed study was performed in 2007 by Denisov et al [64]. The radiation-induced reduction reduces the Fe III to Fe II , but, at this low temperature, the H 2 O that ligates to the iron is unable to move away to generate the normal ferrous deoxy [65] [66].…”
mentioning
confidence: 99%